Supplementary English Reading Materials Based on Interreligious Values in Maluku for the X Grade Students - Sahuleka, Inge (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2022)
This study explores the development of supplementary English reading materials grounded in interreligious values for Grade X students in Maluku, Indonesia. Recognizing the need for educational content that promotes tolerance and interreligious harmony, this research develops and evaluates reading materials that integrate local Maluku cultural values. The materials, designed as procedure, report, and recount texts, incorporate themes that celebrate cooperation and mutual respect among diverse religious communities. Findings indicate that these materials not only improve reading comprehension but also foster students’ appreciation of interreligious harmony, a critical social value in Maluku's multicultural society.